The Cultural Content in EFL Textbooks and What Teachers Need to Do About It (2015)
This article analyzes the cultural content in three communicative English as a foreign language textbooks that are used as main instructional resources in the English classroom. The study examined whether the textbooks include elements of surface or deep culture, and the findings indicate that the textbooks contain only static and congratulatory topics of surface culture and omit complex and transformative forms of culture. Consequently, the second part of the article suggests how teachers can address deep-rooted aspects of culture that might help English as a foreign language learners build more substantive intercultural competence in the language classroom.En este artículo se analiza el contenido cultural en tres textos de inglés comunicativo utilizados como el principal recurso de enseñanza en la clase de inglés. Se indagó si los textos incluyen elementos de la cultura superficial o de la cultura profunda. Se observó que los textos sólo presentan temas “admirables” y representativos de la cultura superficial y no ofrecen temas complejos y trasformativos de la cultura profunda. En consecuencia, en la segunda parte del artículo se sugiere a los profesores de inglés cómo abordar aspectos complejos de la cultura profunda que podrían ayudarle a los estudiantes de inglés como lengua extranjera a construir una competencia intercultural más sólida.